Pengaruh Payment Gateway dan Literasi Keuangan dan Digitalisasi terhadap Kinerja Keuangan pada Pelaku UMKM di Kabupaten Brebes - Dwi Harini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study analyzes the influence of payment gateways, financial literacy, and digitalization on the financial performance of MSME actors in Brebes Regency, especially Mitra Mandiri MSMEs. MSMEs have a significant role in Indonesia's economy, but they still face various challenges, especially in the aspects of financial technology and digital literacy. Payment gateways enable faster and safer transactions, while financial literacy supports better cash flow management and financial planning. Digitalization also plays a role in improving operational efficiency. This study uses a quantitative method with a survey approach to 51 respondents. Data were collected through questionnaires and analyzed by multiple linear regression to test the relationship between variables. The results of the study show that payment gateways and financial literacy have a positive and significant effect on the financial performance of MSMEs. Payment gateways improve transaction efficiency and expand market access, while financial literacy helps in better financial management. However, digitalization does not have a significant influence on financial performance, showing that the implementation of digital technology still faces obstacles in the adoption and optimal utilization by MSME actors. These findings emphasize the importance of increasing the use of payment gateways and financial literacy education for MSME actors to improve their financial performance.